Thrombosis in Pregnant Women with Hematological Malignancies: A Case-Based Review - Krayem, Baher; Brenner, Benjamin; Horowitz, Netanel A. (Seminars in Thrombosis and Hemostasis, 2022)
Cancer and pregnancy induce a procoagulant environment which may lead to maternal and fetal complications, such as venous thromboembolism, fetal growth restriction, and fetal loss. The incidence of hematological malignancies diagnosed during pregnancy is rising, and thrombotic events in such malignancies are not rare. Management of thrombosis during pregnancy poses a therapeutic challenge, that is further exacerbated by the impact of cancer. The available data on managing pregnant women with hematological malignancies are limited to those with myeloproliferative neoplasms, mainly essential thrombocythemia, and, to a lesser extent, polycythemia vera. Low-dose aspirin is recommended throughout pregnancy, and considering treatment with low-molecular-weight heparin and interferon formulations is advised for high-risk patients. Currently, guidelines for handling thrombotic events in pregnant women with lymphoma or leukemia are lacking, and their management is based on data extrapolated from retrospective studies, and guidelines for prevention and treatment of cancer-associated thrombosis. The present case-based review will focus on the complex issue of thrombotic risk in pregnant women with hematological malignancies, specifically myeloproliferative neoplasms, lymphomas, and leukemias.
Keywords: pregnancy; hematological malignancies; thrombosis